Anti‐Inflammatory Effect of Novel 7‐Substituted Coumarin Derivatives through Inhibition of NF‐κB Signaling Pathway. Issue 3 (15th February 2019) - Mu, Chaoyu; Wu, Mingfei; Li, Zeng
Abstract: A series of novel 7‐substituted coumarin derivatives were synthesized and evaluated. Biological screening results obtained by the evaluation of the compounds' inhibition against LPS‐induced IL‐6 and TNF‐α release in RAW 264.7 cells indicated that most compounds exhibited potent anti‐inflammatory activity. Among them, N ‐(3‐methoxybenzyl)‐2‐[(2‐oxo‐2 H ‐chromen‐7‐yl)oxy]acetamide (2d ) showed the best activity. The potential targets of title compound2d were reversely screened with the molecular modeling software, Discovery Studio 2017 R2. Screening and molecule docking results showed that2d could bind to the active site (NLS Polypeptide) of NF‐κB p65, and this binding affinity was confirmed by surface plasmon resonance (SPR) analysis. Furthermore, Western blot assay showed that2d remarkably blocked the NF‐κB signaling pathway in vitro. Collectively, all these findings suggested that compound2d might be a promising lead compound worthy of further pursuit. Abstract :